Development of “-omics” research in Schistosoma spp. and -omics-based new diagnostic tools for schistosomiasis - Wang, Shuqi; Hu, Wei (Frontiers in Microbiology, 2014)
Schistosomiasis, caused by dioecious flatworms in the genus Schistosoma, is torturing people from many developing countries nowadays and frequently leads to severe morbidity and mortality of the patients. Praziquantel (PZQ) based chemotherapy and morbidity control for this disease adopted currently necessitate viable and efficient diagnostic technologies. Fortunately, those “-omics” researches, which rely on high-throughput experimental technologies to produce massive amounts of informative data, have substantially contributed to the exploitation and innovation of diagnostic tools of schistosomiasis. In its first section, this review provides a concise conclusion on the progresses pertaining to schistosomal "omics" researches to date, followed by a comprehensive section on the diagnostic methods of schistosomiasis, especially those innovative ones based on the detection of antibodies, antigens, nucleic acids, and metabolites with a focus on those achievements inspired by "omics" researches. Finally, suggestions about the design of future diagnostic tools of schistosomiasis are proposed, in order to better harness those data produced by "omics" studies.